(untitled) (Research, Society and Development, 2022)
Objective: This study aims to identify evidence on sleep restriction with the development of metabolic diseases available in the literature in the Latin American context. Methods: An integrative literature review was carried out by searching the PubMed, BVS, Scopus, and Web of Science databases. The search strategy was developed from the Descriptors in Health Sciences (DeCS) “sleep deprivation” and “metabolic syndrome”, as well as their variants in English - “metabolic syndrome” and “sleep deprivation”, was also used. the term “sleep duration.” Scientific articles published from 2017 to 2021 were included, with access to the full text and available in English, Spanish and Portuguese. Results: 14 articles were included based on the inclusion and exclusion criteria, which served as a basis for collecting relevant information for the results, which were exposed to the table. Conclusion: Epidemiological studies have shown that in modern society individuals sleep less and less, the current world situation is the result of several factors, such as such as: work demand, social and economic changes, but sleep restriction is associated with the development of metabolic diseases, through pathophysiological mechanisms that can evolve with pathologies such as obesity and diabetes.